Justice in the Distribution of Inheritance: Perspectives of Islamic Law and the Malaysian Case - Nuurussyifa, Nuurussyifa; Fatimah, Fatimah (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2024)
This research discusses the considerations in making a decision by the High Court in Malaysia regarding claims for inheritance rights to the inheritance of his late mother according to farid law and law in Malaysia based on Islamic law. However, in these considerations the Court rejected the claim for several reasons. The research method used is descriptive qualitative research related to Islamic law and law in Malaysia. The results of decisions and law books in this research are used as sources of information. The decision made by the High Court in the claim for heirs' rights was unacceptable and unfair. This is because the arguments in the trial were not based on Islamic law and the laws in Malaysia. In fact, the High Court should be careful in giving decisions so as not to have a negative impact on other heirs. This research aims to determine the rights of heirs who are eligible to receive inheritance according to Islamic law and the law used in Malaysia regarding assets left behind by the deceased. [Studi ini membahas tentang pertimbangan dalam mengambil keputusan oleh Mahkamah Tinggi di Malaysia mengenai tuntutan hak kewarisan ke atas warisan mendiang ibunya menurut hukum faraid dan hukum di Malaysia berdasarkan hukum Islam. Namun, dalam pertimbangan tersebut pihak Mahkamah telah menolak tuntutan tersebut dengan beberapa alasan. Metode penelitian yang digunakan adalah penelitian kualitatif deskriptif berkaitan dengan hukum Islam dan hukum di Malaysia. Hasil keputusan dan buku hukum dalam penelitian ini digunakan sebagai sumber informasi. Putusan yang ditetapkan oleh pihak Mahkamah Tinggi dalam tuntutan hak ahli waris tersebut adalah tidak relaven dan tidak adil. Hal ini dikarenakan, argumen di dalam sidang tidak berasaskan hukum Islam dan undang-undang di Malaysia. Justru itu, Mahkamah Tinggi seharusnya berhati-hati dalam memberikan putusan agar tidak menimbulkan dampak negatif terhadap ahli waris lainnya. Penelitian ini bertujuan untuk mengetahui hak-hak ahli waris yang layak menerima harta warisan menurut hukum Islam dan hukum yang digunakan di Malaysia mengenai harta sepeninggalan Almarhumah.]